The influence of emotion on working memory: Exploratory fMRI findings among men with histories of childhood sexual abuse. (December 2021) - Chiasson, Carley; Moorman, Jessie; Romano, Elisa; Vezarov, Michel; Cameron, Andrew; Smith, Andra
Abstract: Background: Childhood maltreatment can have detrimental consequences on individual well-being and cognitive functioning. One type of childhood maltreatment that remains stigmatized and under-researched among men is child sexual abuse (CSA). Research examining the neurophysiological consequences of CSA in males is limited even further. Objective: To provide preliminary insight into the neural basis of the impact of CSA during two working memory tasks. Participants and setting: Men with CSA histories, with and without post-traumatic stress disorder (PTSD; CSA + PTSD n  = 7, mean age = 45; CSA-PTSD; n  = 9, mean age = 41), and men without a CSA history nor PTSD ( n  = 13, mean age = 36) participated in the study at a local hospital. Methods: Participants completed a letter n-back task and an emotional picture n-back task during fMRI to measure working memory and the influence of emotion on working memory. They also completed self-report measures to assess mental health and childhood abuse histories. Results: In the letter n-back task, men with CSA + PTSD had less activation in the cerebellum and left fusiform gyrus compared to CSA-PTSD men. During the working memory task with negative emotional pictures the control group had greater frontal activation, while the CSA-PTSD group had greater limbic activation. Analyses were performed with independent-samples t -tests. Conclusions: This study provides preliminary empirical evidence of the impact CSA can have on men regarding working memory when negative stimuli are involved. It highlights that CSA, even without a diagnosis of PTSD, can have a significant neurophysiological impact. It also provides clinicians with information to support well-being and help with potential day to day challenges.